2021
DOI: 10.1186/s12968-021-00710-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in COVID-19 patients: mid-term follow up by cardiovascular magnetic resonance

Abstract: Background Coronavirus disease 2019 (COVID-19) induces myocardial injury, either direct myocarditis or indirect injury due to systemic inflammatory response. Myocardial involvement has been proved to be one of the primary manifestations of COVID-19 infection, according to laboratory test, autopsy, and cardiovascular magnetic resonance (CMR). However, the middle-term outcome of cardiac involvement after the patients were discharged from the hospital is yet unknown. The present study aimed to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
147
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(194 citation statements)
references
References 36 publications
(15 reference statements)
12
147
2
6
Order By: Relevance
“…Despite the relative lack of studies examining the long-term impact of SARS-CoV-2 on cardiovascular system, existing evidence suggests an increased rate of major adverse cardiovascular events in recovered COVID-19 patients after a median follow-up of 140 days [76]. In another study, in accordance with previous data for subacute complications, myocardial injury was detected in 30% of patients at 3-month follow-up after COVID-19 infection [77]. Moreover, postural orthostatic tachycardia syndrome has been observed in recovered patients who still experience significant disability even 6-8 months after acute infection [78].…”
Section: Cardiovascular Systemsupporting
confidence: 67%
“…Despite the relative lack of studies examining the long-term impact of SARS-CoV-2 on cardiovascular system, existing evidence suggests an increased rate of major adverse cardiovascular events in recovered COVID-19 patients after a median follow-up of 140 days [76]. In another study, in accordance with previous data for subacute complications, myocardial injury was detected in 30% of patients at 3-month follow-up after COVID-19 infection [77]. Moreover, postural orthostatic tachycardia syndrome has been observed in recovered patients who still experience significant disability even 6-8 months after acute infection [78].…”
Section: Cardiovascular Systemsupporting
confidence: 67%
“…In this setting, patients may present a decreased LV ejection fraction, increased LV volumes, and raised native T1 and T2. Wang et al [173] confirmed these results in a small cohort of patients evaluated with CMR three months after recovery: LGE was found in 30% of them. These patients had significantly decreased LV peak global circumferential strain (GCS), RV peak both GCS and GLS as compared to non-LGE patients, while no difference was found between the non-LGE patients and healthy controls.…”
Section: Cardiovascular Magnetic Resonancementioning
confidence: 64%
“…These patients had significantly decreased LV peak global circumferential strain (GCS), RV peak both GCS and GLS as compared to non-LGE patients, while no difference was found between the non-LGE patients and healthy controls. Lesions were located in the mid myocardium and/or sub-epicardium with a scattered distribution [173]. In the so far largest prospective observational cohort study, Puntmann et al [174] has described abnormal CMR findings, including raised myocardial native T1, raised myocardial native T2, myocardial LGE, or pericardial enhancement.…”
Section: Cardiovascular Magnetic Resonancementioning
confidence: 99%
“…In our study, this contributed to the difference in scar detection rate or scar amount between the proposed method and the manual analysis. Utilization of the ECV map as a guide especially helps the analysts when quantifying the LGE scar with a relatively unknown distribution [6,7,[12][13][14][15][16]. Third, the excellent reproducibility of ECV-guided LGE analysis is an advantage in the systematic detection of small changes in scar size for the monitoring and management of non-ischemic patients, as well as to determine the prognostic risk of patients more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Replacement brosis of left ventricular (LV) scar quanti ed by the amount of late gadolinium enhancement (LGE) has been shown to be a better predictor of the risk of incident adverse clinical events than the presence/absence of LGE alone in different cardiac diseases [1][2][3][4]. However, quanti cation of LGE scar is challenging when the scar distributions are diffuse and patchy, which is typical in nonischemic cardiomyopathy such as myocarditis [5][6][7], cardiomyopathies [8][9][10][11], and in human immunode ciency virus (HIV) cohorts [12][13][14][15][16]. As a result, the quanti cation of scar mass or even the identi cation of LGE can present a huge challenge in non-ischemic cases.…”
Section: Introductionmentioning
confidence: 99%